2012
DOI: 10.1093/schbul/sbs150
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Injectable vs Oral Antipsychotics for Relapse Prevention in Schizophrenia: A Meta-Analysis of Randomized Trials

Abstract: In RCTs, which are less representative of real-world patients than naturalistic studies, pooled LAIs did not reduce relapse compared with OAPs in schizophrenia patients. The exceptions were FGA-LAIs, mostly consisting of fluphenazine-LAI studies, which were all conducted through 1991. Because this finding is vulnerable to a cohort bias, studies comparing FGA-LAI vs second-generation antipsychotics-LAI and LAI vs OAP RCTs in real-world patients are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
254
9
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(279 citation statements)
references
References 44 publications
8
254
9
8
Order By: Relevance
“…Meta-analysis of previous RCTs examining LAI vs OAP do not show significant results (Kishimoto et al, 2012). However, the patient population selected for these trials (clinically stable and motivated for treatment) may not be representative of the patient group for whom clinicians would choose LAIs.…”
Section: Limitationsmentioning
confidence: 96%
“…Meta-analysis of previous RCTs examining LAI vs OAP do not show significant results (Kishimoto et al, 2012). However, the patient population selected for these trials (clinically stable and motivated for treatment) may not be representative of the patient group for whom clinicians would choose LAIs.…”
Section: Limitationsmentioning
confidence: 96%
“…Although there has been conflicting evidence regarding the superiority of LATs over oral antipsychotics (Leucht et al 2011;Kishimoto et al 2013Kishimoto et al , 2014, the outcomes of these studies are highly related to the trial design (Kirson et al 2013). Naturalistic and pragmatic studies, such as the current and other recent studies in acute and nonacute patients with schizophrenia (Schreiner et al 2014, provide valuable information in populations more akin to those encountered in routine clinical practice , by allowing patients with relevant comorbidities, co-medications and substance abuse to be included.…”
Section: Discussionmentioning
confidence: 99%
“…Significant reductions in health care utilization or costs associated with schizophrenia have been demonstrated in some studies of LAI antipsychotics, although other studies have not demonstrated these effects and showed cost-neutrality or even greater cost usually in context with the type of study (eg, observations of naturalistic studies contrary to randomized controlled studies). 31,32 Recently, two new LAI formulations of second-generation antipsychotics have become available, aripiprazole lauroxil (Aristada) and 3-month paliperidone palmitate (Invega Sustenna and Invega Trinza). In October, 2015, the US Food and Drug Administration approved aripiprazole lauroxil, a prodrug of aripiprazole, for the treatment of adults with schizophrenia.…”
Section: New Formulations Of Antipsychoticsmentioning
confidence: 99%